Protein-protein interactions as determinants of operon architecture - Bedi, Silky; Rose, S.M.; Kaur, Simerpreet; Negi, Preeti; Sinha, Sharmistha (Biochimica et biophysica acta. General subjects, 2025)
Operons, clusters of genes under a single promoter, often exhibit a specific gene order influencing their physiological function. While functional relatedness is a known factor for clustering, the underlying drivers of gene ordering remain unclear. To investigate this, we analyzed the pdu operon, encoding proteins for 1,2 Pdu bacterial microcompartment. Our bioinformatics revealed no link between the sequence similarity and proximity of the genes in the operon. However quantitative mapping of protein-protein interactions within the operon using a barrage of spectroscopic tools showed a strong correlation between interaction strength and gene proximity. Our data thus indicates that protein-protein interactions play a significant role in determining gene order within the pdu operon, potentially contributing to the efficient assembly and function of these microcompartments. [Display omitted] •Gene order in the pdu operon is optimized for assembly, with adjacent genes showing stronger protein interactions.•Strong protein interactions form nanotubes, while weaker ones lead to less defined assemblies.•The study offers a framework for bioengineering, enabling synthetic bacterial microcompartments.